A diamond in the desert - Fitzmaurice, Kathryn (Viking, 2012)
After the bombing of Pearl Harbor, thirteen-year-old Tetsu and his family are sent to the Gila River Relocation Center in Arizona where a fellow prisoner starts a baseball team, but when Tetsu's sister becomes ill and he feels responsible, he stops playing.